Maharashtra State BoardSSC (English Medium) 9th Standard
Advertisement Remove all ads

If P ( Y ) = 2 Y 3 − 6 Y 2 − 5 Y + 7 Then Find P ( 2 ) . - Algebra

Sum

If `p(y) = 2y^3 - 6y^2 - 5y + 7` then finf p(2).

Advertisement Remove all ads

Solution

`p(y) = 2y^3 - 6y^2 - 5y + 7` 

`therefore p(2) = 2 xx (2)^3 - 6 xx (2)^2 - 5 xx 2 + 7
= 16 - 24 - 10 + 7 = - 11`

Concept: Value of a Polynomial
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Balbharati Mathematics 1 Algebra 9th Standard Maharashtra State Board
Chapter 3 Polynomials
Practice Set 3.4 | Q 4 | Page 48
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×